ANALISIS TANTANGAN DAN HAMBATAN DALAM IMPLEMENTASI SISTEM INFORMASI PEMERINTAH DAERAH REPUBLIK INDONESIA (SIPD RI) UNTUK PENATAUSAHAAN KEUANGAN DI DINAS CIPTA KARYA, TATA RUANG DAN PERTANAHAN KABUPATEN KOTAWARINGIN TIMUR - Fitria Triwahyuni,; Yuli Fatmawati, (Nusantara Hasana Journal, 2024)
This study aims to analyze the various challenges and obstacles faced in the implementation of the Regional Government Information System Republic Indonesia (SIPD RI) for financial administration in Human Settlements and Spatial Planning Agency (DCKTRP)The background of this study is based on the urgent need to improve transparency, accountability, and efficiency in regional financial management through the use of information technology. This is in line with the demands for modernization of governance, especially in terms of more efficient and accurate financial management. The research method used is a descriptive qualitative approach, in which researchers conducted direct observations, in-depth interviews, and documentation studies from the (DCKTRP) of Kotawaringin Regency. The findings of this study indicate that although SIPD RI was designed with the aim of accelerating the reporting process and facilitating access to financial data, its implementation still faces a number of significant obstacles. These obstacles include the limitations of inadequate technological infrastructure, lack of human resource competence in operating the system, and technical problems that interfere with the accessibility of several important features in SIPD RI. In addition, internal bureaucratic obstacles also slow down the response to problems that arise during the implementation process. From the results of this study, it is concluded that in order to achieve SIPD RI optimization, more serious efforts are needed to improve human resource competency through intensive training, strengthening technological infrastructure, and adjusting to more flexible operational procedures. Thus, SIPD can achieve its main goal of increasing transparency, accountability, and efficiency of regional financial management in real time, which will ultimately provide great benefits for regional financial management in Human Settlement and Spatial palnning Agency (DCKTRP) Kotawaringin Timur